2019
DOI: 10.1039/c9ra04230j
|View full text |Cite
|
Sign up to set email alerts
|

Development of an acetone sensor using nanostructured Co3O4 thin films for exhaled breath analysis

Abstract: We report the fabrication of a breath sensor using nanostructured Co3O4 thin films for the detection of acetone in exhaled breath, which is one of the prominent bio-markers of Diabetic Ketoacidosis (DKA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…The Occupational Safety and Health Administration states that the allowable human exposure level of acetone is 1000 ppm in industries. Different nanostructured cobalt oxide sensing elements were synthesized using a spray pyrolysis method at different deposition temperatures (473 to 773 K) [ 117 ]. It was found that the nanostructured material was more sensitive to acetone when analyzing different solvents such as acetone, EtOH, NH 3 , xylene, toluene, and acetaldehyde.…”
Section: Nanosensor Array E-nose For Exhaled Breath Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The Occupational Safety and Health Administration states that the allowable human exposure level of acetone is 1000 ppm in industries. Different nanostructured cobalt oxide sensing elements were synthesized using a spray pyrolysis method at different deposition temperatures (473 to 773 K) [ 117 ]. It was found that the nanostructured material was more sensitive to acetone when analyzing different solvents such as acetone, EtOH, NH 3 , xylene, toluene, and acetaldehyde.…”
Section: Nanosensor Array E-nose For Exhaled Breath Diagnosismentioning
confidence: 99%
“…The Occupational Safety and Health Administration states that the allowable human exposure level of acetone is 1000 ppm in industries. Different nanostructured cobalt oxide sensing elements were synthesized using a spray pyrolysis method at different deposition temperatures (473 to 773 K) [117]. It was found that the nanostructured material was more Nanostructured materials with various morphologies, including nanorods, nanowires, nanosheets, and nanofibers, have been developed for e-nose applications because their large surface area-to-volume greatly facilitates the conversion of gas response into electric signals.…”
Section: Metal Oxide-based Electrochemical Sensor Array For Disease Diagnosismentioning
confidence: 99%
“…[ 7 ] Indeed, the presence of 1.8 ppm of acetone in exhaled breath indicates the Diabetic Ketoacidosis (DKA). [ 8 ] Another highly toxic and harmful volatile inorganic compound, which is also extremely dangerous for plants, aquatic and land animals and for human health, is nitrogen dioxide (NO 2 ). The main source of NO 2 is the combustion of fossil fuels and the exhaust of motor engines.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 1.8 ppm of acetone in exhaled breath indicates the diabetic ketoacidosis (DKA). [ 21 ] Moreover, as acetone possess fat metabolic nature its concentration dependence on the exhaled breath can also be correlated to the fat loss. [ 22 ] If the exhaled breath analysis shows the presence of more than 1.71 ppm of acetone, then the patient is suffering from type‐2 diabetic mellitus, while 2.19 ppm of acetone in exhaled breath is the indication of type‐1 diabetes.…”
Section: Introductionmentioning
confidence: 99%